German Exports to the Euro Area - A Cointegration Approach - Sabine Stephan (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2005)
This paper analyses the determinants of German exports to the euro area, which is by far the biggest market for German products. Four conditional error-correction models based on regionally disaggregated data are developed. One specification includes EMU industrial production and a real external value based on consumer prices, the other three use different EMU investment aggregates, the corresponding real external values and a proxy for European market integration to explain exports. The models perform equally well in a number of diagnostic tests. For short-term forecasts, however, the model using industrial production seems to be the best, since it outperforms the other models in terms of one-step ahead out-of-sample forecasts. Furthermore, the explanatory variables of this equation (industrial production and consumer prices) are easier to forecast than investment aggregates and the corresponding prices.
urn:nbn:de:101:1-2008081492
Keywords: C22; C52; F47; 330; Export Function; Income and Price Elasticity of Exports; Intra-EMU Trade; Error Correction Model; Forecasting